Joint heritability of sleep EEG spindle activity and thalamic volume in early adolescence - Marković, Andjela; Veen, Duco; Hamann, Christoph; Adorjan, Kristina; Kaess, Michael; O’Gorman, Ruth Tuura; Tarokh, Leila (The journal of neuroscience, 2025)
Sleep spindles, transient bursts of rhythmic activity during non-rapid eye movement sleep, are generated by the thalamocortical network through an intricate interplay between the thalamus and the cortex. Emerging research has shed light on the role of sleep spindles in cognitive function, memory consolidation, and overall brain health. Using a behavioral genetics approach in female and male adolescent humans, this study examined the degree to which sleep spindles (measured via high-density sleep electroencephalography) and thalamic volume (measured via magnetic resonance imaging) are driven by common genetic and environmental factors. Here we show a strong correlation between thalamic volume and sleep spindle amplitude and density. Bayesian structural equation modeling estimated that over posterior regions, genetic factors accounted for approximately half of the covariance between sleep spindle activity and thalamic volume. Our findings demonstrate that genetic factors play a role in shaping the structural and functional integrity of the thalamocortical network, with implications for understanding how these processes contribute to neurodevelopmental outcomes.